DESIGN OF AN ANDROID-BASED QUIZ GAME APPLICATION FOR INTRODUCING GCD AND LCM USING THE LCM METHOD - Robbi Gunawan; Khairunnisa (Ninety Media Publisher, 2026)
Learning Greatest Common Divisor (GCD) and Least Common Multiple (LCM) concepts often presents challenges for students due to conventional teaching methods that are less interactive and engaging. This study aims to design and develop an Android-based quiz game application for introducing GCD and LCM concepts using the Linear Congruential Method (LCM). The proposed application was developed as an interactive educational medium to improve students’ understanding and learning motivation through a game-based approach. The Linear Congruential Method was implemented to randomize quiz questions, ensuring varied question sequences and reducing repetition during gameplay. The application consists of several main features, including a home page, quiz gameplay, learning materials, high score tracking, and developer information. Additionally, immediate feedback mechanisms were integrated to indicate correct and incorrect answers, enabling students to learn from their mistakes directly. The implementation results show that the application successfully provides an interactive and engaging learning experience for students in understanding GCD and LCM concepts. Furthermore, the integration of question randomization using LCM contributes to creating a more dynamic learning process and increasing user engagement. Therefore, the developed application can serve as an alternative educational medium to support mathematics learning in a more effective and enjoyable manner.